2013
DOI: 10.1016/j.jbankfin.2013.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Bank regulatory capital and liquidity: Evidence from US and European publicly traded banks

Abstract: The theory of financial intermediation highlights various channels through which capital and liquidity are interrelated. Using a simultaneous equations framework, we investigate the relationship between bank regulatory capital and bank liquidity measured from on-balance sheet positions for European and U.S. publicly traded commercial banks. Previous research studying the determinants of bank capital buffer has neglected the role of liquidity. On the whole, we find that banks decrease their regulatory capital r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
272
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(307 citation statements)
references
References 41 publications
31
272
1
3
Order By: Relevance
“…The value of equity has proven signifi cant in the creation of liquidity only for the group of large banks with a negative infl uence. This negative relation to the creation of liquidity is in accordance with the fi ndings of other studies (see Berger and Bouwman, 2009;Distinguin, Roulet and Tarazi, 2013;Lei and Song, 2013 etc.). In the remaining two groups, equity was signifi cant only in the case of outfl ow (Tab.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The value of equity has proven signifi cant in the creation of liquidity only for the group of large banks with a negative infl uence. This negative relation to the creation of liquidity is in accordance with the fi ndings of other studies (see Berger and Bouwman, 2009;Distinguin, Roulet and Tarazi, 2013;Lei and Song, 2013 etc.). In the remaining two groups, equity was signifi cant only in the case of outfl ow (Tab.…”
Section: Resultssupporting
confidence: 92%
“…These two concepts have been subjected to many studies. Distinguin, Roulet and Tarazi (2013) explored the relationship of these variables on US and European banks and demonstrated a negative relationship. A negative relationship is also demonstrated by Lei and Song (2013), who explore the Chinese banking market.…”
Section: Studies Dealing With Liquidity Determinantsmentioning
confidence: 99%
“…They used multivariate dynamic panel regression framework and found that macroeconomic variables particularly the monetary policy indicators had a strong negative effect on liquidity creation, and bank specific variables like bank financial performance and size did not affect liquidity creation. Distinguin et al (2013) investigated the relationship between bank regulatory capital and liquidity measured from on-balance-sheet activities. They used the data of US and European publically traded commercial banks spanning 2000 to 2006.…”
Section: Studies Regarding Bank Liquidity Creationmentioning
confidence: 99%
“…Recent studies confirm that banks might hold liquidity as insurance against shocks and use it as a buffer, limiting the need for additional capital (Jokipii and Milne, 2011), while other banks (such as small banks) might increase capital to compensate for a lack of liquidity (Distinguin et al, 2013).…”
Section: Number Of Inspectionmentioning
confidence: 99%